South India political parties influence on India’s Foreign Policy of Tamil Separatism in Sri Lanka - Wijekoon, Whmck; Pramono, B.; Hadisancoko, R. E. (Technium Social Sciences Journal, 2023)
Close relationships between the Sri Lankan Tamil community and the Tami communities in South India have resulted in the involvement of South Indian political parties in the Tamil problem in Sri Lanka. This involvement has continued even after the defeat to Tamil terrorists by the Sri Lankan military and is primarily concerned with influencing Indian foreign policy on the separatism issue in Sri Lanka. The main objectives of this study were to identify the factors which are motivating South Indian political parties to influence Indian foreign policy on separatism in Sri Lanka and to identify the strategies used by South Indian political parties to influence Indian Central Government foreign policy on separatism in Sri Lanka. Research method to achieve these two objectives was a qualitative method. This research method consisted of collecting non-numeric data from individuals with significant knowledge of South Indian political parties and analysing the collected data using quantitative content analysis. Findings from the study revealed that there are several factors motivating South Indian political parties to influence foreign policy on separatism in Sri Lanka. These factors are namely genuine concern for the plight of Sri Lankan Tamils, political self-interest, financial factors, social and humanitarian factors. Findings from the study also revealed that the main strategies adopted by South Indian political parties to influence Indian foreign policy on separatism are to threaten to withhold support to the ruling party in the Lok Shaba and prevent/disrupt the implementation of national projects in South Indian states.